Repetitive transcranial magnetic stimulation for the treatment of cognitive impairment in frontotemporal dementia: an open-label pilot study - Antczak J (Dove Medical Press, 2018)
Jakub Antczak,1 Katarzyna Kowalska,1 Aleksandra Klimkowicz-Mrowiec,1 Barbara Wach,2 Katarzyna Kasprzyk,1 Marta Banach,1 Karolina Rzeźnicka-Brzegowy,3 Jadwiga Kubica,3 Agnieszka Słowik1 1Department of Neurology, Jagiellonian University Medical College, Kraków, Poland; 2Department of Neurology, 5th Military Hospital with Polyclinic in Cracow, Kraków, Poland; 3Institute of Physiotherapy, Faculty of Health Sciences, Jagiellonian University Medical College, Kraków, Poland Background: Frontotemporal dementia (FTD) is one of the most frequent dementia types in patients under 65 years of age. Currently, no therapy can effectively improve the cognitive deficits associated with FTD. Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive method of inducing brain plasticity with therapeutic potential in neurodegenerative diseases. The purpose of this study was to evaluate the effect of rTMS on cognitive, behavioral, and emotional function in FTD. Methods: Nine patients (seven women, four men, mean age 61.7±10.1 years) with the behavioral variant of FTD, one with nonfluent/agrammatic variant primary progressive aphasia, and one with progressive nonfluent aphasia (subtypes of FTD) underwent 10 daily sessions of 10 Hz rTMS over the bilateral dorsolateral prefrontal cortex. Cognitive and behavioral assessments were administered before and after therapy. Results: After rTMS, the Montreal Cognitive Assessment and letter and digit cancellation test scores, as well as reading time and error number in the Stroop test improved. The caregivers’ impression of the daily functioning of patients improved in the Frontal Behavioral Inventory scores. These changes were not paralleled by an improvement of mood. Conclusion: The results indicate that rTMS may improve the cognitive performance of patients with FTD and warrant sham-controlled trials. Keywords: frontotemporal dementia, repetitive transcranial magnetic stimulation, Montreal Cognitive Assessment